Spatiotemporal characteristics and spatial heterogeneity of influencing factors in China’s urbanization process: based on nighttime light remote sensing data - Ren, Zhou; Zhang, Cancan; Fan, Long; Zhao, Xiaonan (Frontiers in Environmental Science, 2025)
IntroductionThe process of urbanization involves all aspects of society and understanding the spatial differences in urban development is crucial to promoting sustainable urban development. However, the existing studies still lack a spatial heterogeneity analysis of the driving factors of urbanization at the prefectural-level city scale and over a long period of time.MethodsThis study uses nighttime light data, with 285 prefecture-level cities in China as the research objects. It employs spatial autocorrelation and the geographically weighted regression (GWR) model to investigate the spatial heterogeneity of the factors influencing urban development in China from 2000 to 2019.Results(1) The overall level of urbanization in China is on the rise. Spatially, it exhibits a distribution pattern shifting from concentration to dispersion and from a single center to multiple centers. (2) The urbanization process in China exhibits a significant spatial correlation. The hotspots are mainly concentrated in the eastern part of China along the southern coast and the northern part of the southern coast, while the coldspots are located in the southwestern, northwestern, and northeastern regions. (3) The regression coefficients of the influencing factors exhibit significant spatial imbalance. Economic development, population size, public infrastructure, and economic openness all show a positive correlation with urbanization development as a whole; the industrial structure has a negative impact on urbanization development in most regions, and its inhibitory effect is weakest in the cold spots.DiscussionCapturing this heterogeneity is of vital importance for understanding the diverse paths of urban development and formulating differentiated policies for specific regions.